Electoral authoritarianism and economic control. Issue 1 (January 2018) - Seeberg, Merete Bech
While electoral revolutions in the Philippines and the post-Communist world have ousted dictators, autocrats from Mexico to Zimbabwe have cemented their rule through regular multi-party elections. Why do elections sometimes undermine authoritarian regimes while at other times they help sustain them? I argue that a dictator's control over the economy conditions the effect of authoritarian elections. Where rulers command the heights of the economy, elections are more easily manipulated to sustain their rule. But where such control is lacking, elections may spur regime change. In a cross-national study of autocracies from 1970 to 2006, I find that as incumbent control over the economy increases, elections are less likely to lead to regime breakdown. Where economic control is at its lowest, elections increase the risk of regime collapse. Thus, research on authoritarianism needs to supplement the study of authoritarian regime types and institutional characteristics with a focus on the rulers' control over the state and the economy.